2013
DOI: 10.3109/09638288.2012.753116
|View full text |Cite
|
Sign up to set email alerts
|

Car driving in schizophrenia: can visual memory and organization make a difference?

Abstract: The research demonstrates that impairment of visual abilities does not prevent people with schizophrenia from driving and emphasizes the importance of general cognitive status for complex and multidimensional everyday tasks. The findings support the need for further investigation in the field of car driving for this population - a move that will considerably contribute to the participation and well-being. Implication for Rehabilitation Unique approach for driving evaluation in schizophrenia should be designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…These findings highlight the role of EF as cognitive skills required for driving, a complex activity based on coordination, perception, organization, and planning (Asimakopulos et al, 2012;Butler, Silverstein, & Dakin, 2008;Lipskaya et al, 2013). Similar findings on the relationship between driving skills and EF have been found in other populations, for example, people with dementia, multiple sclerosis, and traumatic brain injury (Coleman et al, 2002;Freund, Colgrove, Petrakos, & McLeod, 2008;Lincoln & Radford, 2008;Patomella, Kottorp, & Tham, 2008).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings highlight the role of EF as cognitive skills required for driving, a complex activity based on coordination, perception, organization, and planning (Asimakopulos et al, 2012;Butler, Silverstein, & Dakin, 2008;Lipskaya et al, 2013). Similar findings on the relationship between driving skills and EF have been found in other populations, for example, people with dementia, multiple sclerosis, and traumatic brain injury (Coleman et al, 2002;Freund, Colgrove, Petrakos, & McLeod, 2008;Lincoln & Radford, 2008;Patomella, Kottorp, & Tham, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, people with schizophrenia and schizoaffective disorder frequently experience decreased cognitive functioning, including executive function (EF), as an inherent part of their health condition. Research has shown that cognitive impairments affect performance of wide range of everyday activities in general and driving in particular (Bozikas, Kosmidis, Kiosseoglou, & Karavatos, 2006;Green, Kern, & Heaton, 2004;Lipskaya et al, 2013;Palmer et al, 2002).…”
mentioning
confidence: 99%
“…Currently, it is also unclear whether speed processing deficits in schizophrenia impact other aspects of functioning in dynamic visual environments. Some evidence suggests patients experience twice as many car accidents compared to other drivers (Edlund et al, 1989; Lipskaya-Velikovsky et al, 2013). The Flash Lag illusion demonstrates that judgments of the relative position between stationary and moving objects are affected by motion speed.…”
Section: Introductionmentioning
confidence: 99%
“…The constructional apraxia uncovered by the CFT was not secondary to visual agnosia as evidenced by the DROT findings. Although the employed tasks did not constitute real life challenges, our findings may have clinical significance in patients with schizophrenia because difficulties with perceptual ( 43 ) and spatial integration along with other neurocognitive deficits may be a potential explanation for heightened rates of car accidents ( 44 ) in schizophrenics considering that proper copying cube ability ( 45 ) and left-right orientation ( 46 , 47 ) are important prerequisites for safe driving. Such deficits may relate to lateralized brain dysfunction in these patients ( 48 ) that has some basis in altered brain connectivity ( 49 ).…”
Section: Discussionmentioning
confidence: 91%